The COVID-19 consumption game-changer: Evidence from a large-scale multi-country survey - Alexander Hodbod; Cars H. Hommes; Stefanie J. Huber; Isabelle Salle (European Central Bank (ECB), 2021)
Prospective economic developments depend on the behavior of consumer spending. A key question is whether private expenditures recover once social distancing restrictions are lifted or whether the COVID-19 crisis has a sustained impact on consumer confidence, preferences, and, hence, spending. The elongated and profound experience of the COVID-19 crisis may durably affect consumer preferences. We conducted a representative consumer survey in five European countries in summer 2020, after the release of the first wave's lockdown restrictions, and document the underlying reasons for households' reduction in consumption in five key sectors: tourism, hospitality, services, retail, and public transports. We identify a large confidence shock in the Southern European countries and a shift in consumer preferences in the Northern Eu-ropean countries, particularly among high-income earners. We conclude that the COVID-19 experience has altered consumer behavior and that long-term sectoral consumption shifts may occur.
Keywords: D12; D81; D84; E21; E60; E71; G51; H30; 330; COVID-19; household behavior; consumption; expectations; experiences; consumer preferences; economic resilience; sectoral changes; zombification; fiscal policy